USING YOUTUBE VIDEOS TO IMPROVE STUDENTS’ PRONUNCIATION AT SMPN 3 BAEBUNTA - Rahman, Ufia Ananda; Abduh, Amirullah; Muhayyang, Maemuna (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The research aimed to investigate whether using YouTube videos improve students' pronunciation ability. Employing a quantitative method with a pre-experimental design, the study focused on students in eighth grade at SMPN 3 Baebunta, with a sample size of 30 students from class 8.A. Data collection involved pre-tests and post-tests. The analysis revealed a notable increase in post-test mean scores compared to pre-test scores, indicating an improvement from a very poor to a good category. Statistical analysis using a t-test with a significance level of 0.05 demonstrated a significant difference between pre-test and post-test scores, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). Thus, according to the study's hypothesis, the utilization of YouTube videos significantly enhanced students' pronunciation skills at SMPN 3 Baebunta. Consequently, the researcher concluded that the use of YouTube videos improved students' pronunciation at SMPN 3 Baebunta.Keywords: Pronunciation,YouTube Videos.